Field emission investigation of composites of polypyrrole with graphene oxide, reduced graphene oxide and graphene nanoribbons - Harpale, Kashmira; Bansode, Sanjeewani; More, Mahendra; Late, D. J. (2016 29th International Vacuum Nanoelectronics Conference (IVNC), 2016)
The monomer pyrrole has been polymerized by chemical route in the presence of graphene oxide (GO), reduced graphene oxide (rGO) and graphene nanoribbons (GNR) separately to prepare nanocomposites as Polypyrrole-GO (PGO), PPy-rGO (PRGO), PPy-GNR (PGNR), respectively. The morphological, chemical and structural characterization of the as-synthesized products was carried out using scanning electron microscopy (SEM), Raman and fourier transform infrared (FTIR) spectroscopy. Field emission (FE) studies of PGO, PRGO, PGNR emitters were performed at the base pressure of 1x10(-8) mbar in planar `diode' configuration. Onset and threshold field values corresponding to emission current densities of 1 and 100 mu A/cm(2) are observed to be 1.5 and 2.3V/mu m for PGO, 1.4 and 2.2 V/mu m for PRGO and lowest for PGNR as 0.9 and 1.2V/mu m, respectively. The maximum emission current density of 2.5 mA/cm(2) drawn for PGO at the applied electric field of 3.2V/mu m, 1.2 mA/cm(2) at 3.6V/mu m from the PRGO and 8 mA/cm(2) at the field of 2.2 V/mu m from the PGNR emitters. An emission current versus time (I-t) plot shows stable emission behavior for the preset current values.
Keywords: field emission; FTIR; polypyrrole; Raman

Nano-heteroarchitectures of two-dimensional MoS 2 @ one-dimensional brookite TiO 2 nanorods: prominent electron emitters for displays - Devan, Rupesh S.; Thakare, Vishal P.; Antad, Vivek V.; Chikate, Parameshwar R.; Khare, Ruchita T.; More, Mahendra; Dhayal, Rajendra S.; Patil, Shankar I.; Ma, Yuan-Ron; Schmidt-Mende, Lukas (ACS Omega, 2017)
We report comparative field electron emission (FE) studies on a large-area array of two-dimensional MoS2-coated @ one-dimensional (1D) brookite (β) TiO2 nanorods synthesized on Si substrate utilizing hot-filament metal vapor deposition technique and pulsed laser deposition method, independently. The 10 nm wide and 760 nm long 1D β-TiO2 nanorods were coated with MoS2 layers of thickness ∼4 (±2), 20 (±3), and 40 (±3) nm. The turn-on field (Eon) of 2.5 V/μm required to a draw current density of 10 μA/cm² observed for MoS2-coated 1D β-TiO2 nanorods emitters is significantly lower than that of doped/undoped 1D TiO2 nanostructures, pristine MoS2 sheets, MoS2@SnO2, and TiO2@MoS2 heterostructure-based field emitters. The orthodoxy test confirms the viability of the field emission measurements, specifically field enhancement factor (βFE) of the MoS2@TiO2/Si emitters. The enhanced FE behavior of the MoS2@TiO2/Si emitter can be attributed to the modulation of the electronic properties due to heterostructure and interface effects, in addition to the high aspect ratio of the vertically aligned TiO2 nanorods. Furthermore, these MoS2@TiO2/Si emitters exhibit better emission stability. The results obtained herein suggest that the heteroarchitecture of MoS2@β-TiO2 nanorods holds the potential for their applications in FE-based nanoelectronic devices such as displays and electron sources. Moreover, the strategy employed here to enhance the FE behavior via rational design of heteroarchitecture structure can be further extended to improve other functionalities of various nanomaterials.

Hydrothermal synthesis of rGO-PbBi2Se4 composite and investigation of its structural, chemical and field emission properties - Aher, Rahul; Bhorde, Ajinkya; Sharma, Priyanka; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Rondiya, Sachin; Chaudhary, Minakshi; Gopinath, Chinnakonda; Suryawanshi, Sachin; More, Mahendra; Jadkar, Sandesh (Journal of Materials Science-Materials in Electronics, 2018)
In the present study we report the one step facile synthesis of pristine lead bismuth selenide (PbBi2Se4) and reduced graphene oxide (rGO) and its composites with PbBi2Se4. Formation of pristine PbBi2Se4 and rGO-PbBi2Se4 composite were confirmed by X-ray diffraction and X-ray photoelectron spectroscopy. The surface morphology and topography investigated by using scanning electron microscopy and transmission electron microscopy revealed the formation of nano-flowers pristine PbBi2Se4. After coupling pristine PbBi2Se4 with rGO the surface morphology shows the formation of sharp vertically protruded nano-sheets/nano-flaks originated from the nano-flowers. Finally, the field emission properties of pristine PbBi2Se4 and rGO-PbBi2Se4 composite have been investigated. It has been observed that the rGO-PbBi2Se4 composite emitter exhibited excellent field emission properties with low turn-on field (similar to 2.8 V/A mu m for 10 A mu A/cm(2)), high emission current density (similar to 1288 A mu A/cm(2) at 3.9 V/A mu m) and superior current stability (similar to 4.5 h for similar to 1 A mu A) compare to pristine PbBi2Se4 emitter. Thus, the facile one step synthesis approach and robust nature of rGO-PbBi2Se4 composite emitter can provide prospects for the future development of large-area emitter applications such as flat-panel-display and vacuum micro/nanoelectronics devices.

Phenazine-containing poly(phenylenevinylene): a new polymer with impressive field emission properties - Chhatre, Shraddha; Ichake, Amol; Harpale, Kashmira; Patil, Sumati; Deshpande, Aparna; More, Mahendra; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2018)
Phenazine-containing poly(phenylenevinylene) (P(PHN-PV)) was synthesized using Wittig-Horner polycondensation of the appropriately designed monomers viz. 5,10-dioctyl-5,10-dihydrophenazine-2,7-dicarbaldehyde and tetraethyl ((2,5-bis((2-ethylhexyl) oxy)-1,4 phenylene) bis(methylene)) bis(phosphonate). The design embraces the specific motivation of incorporating the nitrogen-containing heterocycle viz. .phenazine in poly(phenylenevinylene) backbone. P(PHN-PV) exhibited reversible redox properties. In the field emission measurements performed on the film of P(F'HN-PV), the turn-on field was observed to be 1.93 V/mu m for the current density of 10 mu A/cm(2). The maximum current density of similar to 4.87 mA/cm(2) was achieved at the applied field of 3.84 V/mu m. The emission current showed impressive stability for 6 h at a constant current of 1 mu A (current density of about 20 mu A/cm(2)). These results emphasize the role of phenazine heterocycle with lone pair of electrons on nitrogen in lowering the oxidation onset and in turn reduction of the turn-on voltage.
Keywords: field emission; Phenazine; Poly(phenylenevinylene)